Avaliação da rotulagem de alimentos embalados comercializados no Estado de Minas Gerais nos anos de 2011 e 2012 - Valéria Regina Martins Vieira (2014)
The Consumer Defence Code (Law n. 8.078/90) determines, in its article 31, that the offer and presentation of products must assure correct, precise and clear information about its qualities, characteristics, composition, quantity, price, warranty, expiration dates, and origin, among other information (...). The labeling of foods must provide correct information, since it is associated with the adoption of healthy eating habits and encompasses both the food and nutritional safeties of the consumer. Nowadays, besides providing nutritional information, labeling plays an important role in the decision of buying any food item, being the label the main instrumento of information. They compile data and enable the consumer to make decisions concerning which product they should consume. This work analysed the effectiveness of the basic consumer right to clear and adequate information regarding the labeling of food products. The general objetive consisted of critically analysing the labeling of products sold in the state of Minas Gerais in the years of 2011 and 2012. It was also the objetive of this study to compare the results obtained from the content determinating physicochemical tests of sodium, total carbohydrates, proteins and total fats of the analysed foods with their respective declared values in the labels. The constant failures in the labels were mapped, and it was discussed with a critical basis in relation to the categories of foods common to the two years. It was performed the statistical analysis through the hypothesis test for the difference of proportion with 5% probability, for the categories common to the years of 2011 and 2012, with a minumum of 50 labels. It was still problematized the importance of labeling in face of some non-communicable chronic diseases, such as diabetis mellitus, systemic arterial hypertension and obesity. This work originated from the hypothesis that the labeling of products must be adequate in order to guarantee the consumer its basic right to dietary choices throught the conformity with the current sanitary regulations. It was used as an evaluative method the fulfilment of the mandatory itens demanded in current regulations, by comparing the information and the values described in the labels. It was evaluated the percentage of satisfactory and unsatisfactory labels. Most part of the samples were sent by the Health Surveillance of Minas Gerais, through the Quality Monitoring Programme PROG VISA, with a total 2371 samples. It was performed the analysis of all the labels and it was made a critical evaluation of the categories of the analysed foods, with an minimum of 50 labels added to the two years, totalling 17 categories (mineral water, peanuts and derivatives, cookies, ground coffee, sweets, spices, tomato sauce, iced products, yogurts, pasteurized milk, UHT milk, cheese bread, cheeses, sodas, frozen snacks, soy and derivatives). It was also described the ratio between label / brand in the common categories. It was concluded that there was a high level of failure in the evaluated products (average of 76, 4%), since they did not comply with the current regulations. It becomes evident the need to enforce the labeling regulations, in order to guarantee the basic rights of the consumer, by reducing the number of labeling failures.